Simulator based teaching of Trans-Urethral Resection of Prostate (TURP) skills in urology. - Kashifuddin Qayoom Soomro; Rajpar, Zakir Hussain; Idrees Memon, Imran; Shah, Syed Azhar Hussain; Jat, Javed Altaf; Memon, Shafique Ur Rehman (International Journal of Endorsing Health Science Research, 2021)
Background: After the introduction of simulators in urology, urology education has evolved significantly. The development of Transurethral Resection of Prostate (TURP) skills has shifted to simulator-based learning from being directly on patients. We evaluated the outcome of simulation-based teaching of TURP procedural skills on virtual reality simulator and objectively assessed the operative skills on the Global Rating Scale (GRS). Methodology: In this prospective comparative study, high fidelity (VirtaMed | UroSim™) simulator was used. A total of 17 participants were enrolled in this study, 4 were urology faculty members, and 13 were post-graduate urology trainees. All participants performed five attempts of real-time TURP complete procedure and were allowed to resect the maximum possible prostate tissue (goal ≥ 85%). Skills were assessed in terms of resection, bleeding control and safety parameters. Objective assessment of simulative operative skills was done on GRS score sheets by faculty, based on the Global Rating Index for Technical Skills (GRITS) and OSATS. The data from the 1st and 5th attempts of all participants was analyzed on SPSS version 22.0. Results: There was statistically significant difference in the mean resection score at 1st attempt between faculty and trainees i.e. 112±8.6 and 86.69±9.95, respectively (p<0.01), while the scores were comparative by the 5th attempt. All the enrolled members resected >80% of prostate volume (40 score points). Similarly, for the parameters associated with bleeding control, there was a significant difference in the bleeding control, lost blood and remaining bleeders between trainees and faculty members (p<0.01) at 1st attempt while on 5th attempt, the outcomes were comparative in both groups. The objective assessment of operative skills of the trainee’s displayed improvement in all 5 parameters including tissue injury, movement and time, instrument application, surgical process and surgical details. Conclusion: Simulation-based TURP teaching significantly improves simulative operative skills in resection, bleeding control and safety parameters. GRS is an effective tool in assessing simulative operative skills and may evaluate endo-urological procedural training in urology trainees periodically.